Digital Curation: The Emergence of a New Discipline - Sarah Higgins (International Journal of Digital Curation, 2011)
In the mid 1990s UK digital preservation activity concentrated on ensuring the survival of digital material – spurred on by the US report Preserving Digital Information (The Task Force on Archiving of Digital Information, 1996) and developed through JISC-funded activities. Technical developments and a maturing understanding of organisational activity and workflow saw the emphasis move to ensuring the access, use and reuse of digital materials throughout their lifecycle. Digital Curation emerged as a new discipline supported through the activities of the UK’s Digital Curation Centre and a number of EU 6th Framework Projects. Digital Curation is now embedded in both practice and research; with the development of tools, and the foundation of a number of support units and academic educators offering training and furthering research.